Performance analysis of a suboptimum fast frequency-hopped/M-ary frequency-shift-keying maximum-likelihood receiver over Rician-fading channels with composite effects of partial-band noise jamming and multitone jamming - Li, Kwok Hung (2013)
Bit-error rate (BER) expressions of a suboptimum maximum-likelihood (ML) receiver with the composite effect of partial-band noise jamming and multitone jamming are derived for fast frequency-hopped systems employing M-ary frequency-shift-keying modulation over Rician-fading channels. These BER expressions can be used to study the system performance under Rayleigh fading as a special case. Owing to the fact that the computation of the logarithm of the modified Bessel function is non-linear in nature, one of the existing approximations is required to derive the BER expressions for the analysed system. A suboptimum ML receiver structure is therefore proposed and analysed. The analytical results are compared with simulation results. Under various jamming and fading conditions, the proposed suboptimum ML receiver is found to be able to suppress interference effectively.